Porous becomings anthropological engagements with Michel Serres - Bandak, Andreas; Knight, Daniel M. (Duke University Press, 2024)
One of the foremost intellectuals of his generation, French philosopher of science Michel Serres (1930-2019) broke free from disciplinary dogmas. His reflections on science, culture, technology, art, and religion have proved foundational to scholars across the humanities. The contributors to Porous Becomings bring the inspirational and enigmatic world of Serres to the attention of anthropology. Through ethnographic encounters as diverse as angels and religious conversion in Ethiopia, the percolation of war in Bosnia, and incarcerated bodies crossing the Atlantic, the contributors showcase how Serres's interrogation of the fundamentals of human existence opens new pathways for anthropological knowledge. Proposing the notion of "porosity" to characterize permeability across boundaries of time, space, literary genre, and academic discipline, they draw on Serres to map the constellations that connect humans, time, technology, and planet Earth. The volume concludes with a conversation between the editors and Vibrant Matter author Jane Bennett.Contributors. Andreas Bandak, Jane Bennett, Tom Boylston, Steven D. Brown, Matei Candea, Alberto Corsín Jiménez, David Henig, Michael Jackson, Daniel M. Knight, Celia Lowe, Morten Nielsen, Stavroula Pipyrou, Elizabeth Povinelli, Andrew Shryock, Arpad Szakolczai
Keywords: Serres, Michel -- 1930-2019; SOCIAL SCIENCE / Anthropology / Cultural & Social; Technologie; Kunst; Wissenschaft; Conditio humana; Religion; Kultur; Aufsatzsammlung